EVALUASI KINERJA TRANSJAKARTA KORIDOR VI A Rute Ragunan – Monas (Via Kuningan) - Pariz Salman Danurekso; Prima Jiwa Osly (Jurnal Infrastruktur, 2018)
The growing population of the city of Jakarta to make the movement of people in it. The provision of public transport is indispensable for anticipating congestion will occur. This research aims to determine whether the performance of Transjakarta is in compliance with government rules. When the performance of Transjakarta already in the know results can be communicated to the Government of Jakarta to take a policy so that the performance of Transjakarta growing in his Ministry. This research was conducted in several important stages, include: determining the formulation of the problem, get the collected data the author by way of direct observation survey, then the data obtained were analyzed using the method descriptive and inductive methods, from there we can get the value of the performance of Transjakarta Corridor VI a. The study focused only on one corridor, the VI corridor Ragunan – Monas (Via Kuningan). Observations were then made in Seven days: Monday - Sunday to represent workdays and days off, with each observation day spanning from 7.00 a.m. to 9.00 a.m. According to 100 respondents are analyzed, quality service that satisfies all of the dimensions Tangibles 0.68, Assurance 0.45, Responsiveness 0.50, Reliability 0.66, Emphaty 0.54 have a level of satisfaction performance measurement value Transjakarta by category are very satisfied with the value of all the dimensions of 0.57. Analysis based on the questionnaire distributed to 100 respondents.